Elsewhere - Schaitkin, Alexis, 1985- (Celadon Books, 2022)
"Richly emotive and darkly captivating, with elements of Shirley Jackson's "The Lottery" and the imaginative depth of Margaret Atwood, Elsewhere by Alexis Schaitkin conjures a community in which girls become wives, wives become mothers and some of them, quite simply, disappear. Vera grows up in a small town, removed and isolated, pressed up against the mountains, cloud-covered and damp year-round. This town, fiercely protective, brutal and unforgiving in its adherence to tradition, faces a singular affliction: some mothers vanish, disappearing into the clouds. It is the exquisite pain and intrinsic beauty of their lives; it sets them apart from people elsewhere and gives them meaning. Vera, a young girl when her own mother went, is on the cusp of adulthood herself. As her peers begin to marry and become mothers, they speculate about who might be the first to go, each wondering about her own fate. Reveling in their gossip, they witness each other in motherhood, waiting for signs: this one devotes herself to her child too much, this one not enough--that must surely draw the affliction's gaze. When motherhood comes for Vera, she is faced with the question: will she be able to stay and mother her beloved child, or will she disappear? Provocative and hypnotic, Alexis Schaitkin's Elsewhere is at once a spellbinding revelation and a rumination on the mysterious task of motherhood and all the ways in which a woman can lose herself to it; the self-monitoring and judgment, the doubts and unknowns, and the legacy she leaves behind"--